Analysis of Factors Affecting the Original Income of North Sumatra Province - Khairani BM, Nurul; Irawan, Irawan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the factors that influence the original regional income of North Sumatra province. This study uses quantitative methodology to determine, calculate, and provide quantitative estimates of PAD and regional taxes and regional levies using the SPSS 25 multiple linear regression analysis program. The results of the study indicate that regional taxes have an effect on the Original Regional Income of North Sumatra Province and regional levies have an effect on the Original Regional Income of North Sumatra Province.